Principal's Leadership in Improving Teacher Performance During the Covid-19 Pandemic - La Jaali; Sitti Nurjana Batjo (Syntax Corporation Indonesia, 2023)
Leadership is closely related to the principal as a leader. The behavior of the principal must be able to advance teacher achievement by showing a sense of care, closeness and full attention to the teacher both individually and in groups. This study aims to determine the Principal's Leadership in improving teacher performance during the Covid-19 pandemic (Study at SD AL HILAAL Labuang Timur) Luhutuban Village, West Seram Regency. Data collection techniques in this study used interview, observation and documentation guidelines. Data analysis in this study uses interactive analysis technique models from Miles and Huberman which include the stages of data reduction, data presentation and data verification or drawing conclusions. From the results of this study, it can be concluded that at Al-Hilaal Labuang Timur Elementary School through direct interviews with informants that the Principal has been very good in improving teacher performance in schools. This can be seen in the communication and good relationship between the principal and teachers in the learning process. Although several things were found to be obstacles for principals and teachers in improving teacher performance during Covid-19 conditions, namely limited internet / tower networks, limited electricity (electricity turned on at night), lack of understanding of teachers and students in the use of IT, and limited ownership of mobile phones by teachers and students